A Study of The Density of Motor Vehicles In Front of Bunda Hospital Margonda Depok Against Noise Pollution - Syaiful Syaiful; Noor Wahid (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2020)
Depok became a pilot as an orderly city with traffic arrangements and diverse patterns of population movement. The diversity of the city residents' trips has resulted in an increasingly diverse population passing through the region. Population mobility also requires adequate transportation facilities and infrastructure. This study aims to obtain traffic data and the level of noise pollution caused by the speed of motor vehicles (SPM, MP, MAU) in front of the Bunda Hospital Margonda Depok. The calculation and analysis obtained are on the equation with the first largest R value on the second day of the third point study (Sound Level Meter 3), with a contribution of 50.50%. As equation, y = 73.824 + 0.030x1 - 0.020x2 - 0.324x3, the addition of motorcycle density is 0.030 and the reduction in private car density and public transport car density is 0.344, the noise pollution level will be reduced by 0.314 dBA in SLM3. The second largest R value with motorcycle density, private car density and public transport car density has a moderate effect on noise pollution in the second day of the research point (Sound Level Meter2) with a contribution of 48.50%.